Long Term Seasonal Dynamics of Synechococcus Population Structure in the Gulf of Aqaba, Northern Red Sea - Post, Anton F.; Penno, Sigrid; Zandbank, Keren; Paytan, Adina; Huse, Susan; Mark Welch, David (Frontiers in Microbiology, 2011)
Spatial patterns of marine Synechococcus diversity across ocean domains have been reported on extensively. However, much less is known of seasonal and multiannual patterns of change in Synechococcus community composition. Here we report on the genotypic diversity of Synechococcus populations in the Gulf of Aqaba, Northern Red Sea, over seven annual cycles of deep mixing and stabile stratification, using ntcA as a phylogenetic marker. Synechococcus clone libraries were dominated by clade II and XII genotypes and a total of 8 different clades were identified. Inclusion of ntcA sequences from the GOS database in our analyses identified members of clade XII from beyond the Gulf of Aqaba, extending its known distribution. Most of the Synechococcus diversity was attributed to members of clade II during the spring bloom, while clade III contributed significantly to diversity during summer stratification. Clade XII diversity was most prevalent in fall and winter. Clade abundances were estimated from pyrosequencing of the V6 hypervariable region of 16S rRNA. Members of clade II dominated Synechococcus communities throughout the year, whereas the less frequent genotypes showed a pattern of seasonal succession. Based on the prevailing nutritional conditions we observed that clade I members thrive at higher nutrient concentrations during winter mixing. Clades V, VI and X became apparent during the transition periods between mixing and stratification. Clade III became prominent during sumeer stratification. We propose that members of clades V, VI and X, and clade III are Synechococcus ecotypes that are adapted to intermediate and low nutrient levels respectively. This is the first time that molecular analyses have correlated population dynamics of Synechococcus genotypes with temporal fluctuations in nutrient regimes. Since these Synechococcus genotypes are routinely observed in the Gulf of Aqaba we suggest that seasonal fluctuations in nutrient levels create temporal niches...